(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Myasthenia gravis (MG) is a chronic autoimmune neuromuscular disorder marked by fluctuating muscle weakness and rapid fatigue. Traditional treatments, including anticholinesterase agents, immunosuppressive drugs, and thymectomy, effectively manage symptoms but often come with significant side effects. Complex rehabilitation therapy (CRT) offers a holistic approach, addressing both physical and psychological aspects of MG. CRT encompasses physical, occupational, speech, and respiratory therapies, along with psychological support, tailored to individual patient needs. This comprehensive review evaluates the impact of CRT on muscle strength, functional abilities, and quality of life in MG patients. Evidence suggests that CRT not only enhances physical function and reduces the frequency of myasthenic crises but also significantly improves overall well-being. Integrating CRT into standard care protocols is crucial for optimizing patient outcomes, emphasizing the need for a multidisciplinary approach in MG management.